A comparison of rural–urban differences in out-of-pocket expenses among older Mexicans with diabetes - Rojas Alvarez, Alfonso; Vazquez, Christian E.; Lopez-Ortega, Mariana; Angel, Jacqueline L. (Frontiers in Public Health, 2022)
Objective: To compare total out-of-pocket expenses for physician visits and medications among older adults living with diabetes in Mexico from urban, semi-urban, and rural areas. Methods: The sample includes 2,398 Mexicans 65 and older with self-reported diabetes from the 2018 Mexican Health and Aging Study. Out-of-pocket expenses for physician visits and medications were regressed on locality, controlling for several factors. Results: The profile of those with higher out-of-pocket medication expenditures included rural localities, higher education, unmarried, depressive symptoms, participation in Seguro Popular, and lacking insurance. Rural older adults with diabetes paid a higher amount in medication expenditures compared to other localities. Taking diabetes medication was associated with lower out-of-pocket physician visit expenditures and higher out-of-pocket medication expenditures in rural areas. Conclusions: Differences in locality are closely tied to the effective implementation of Seguro Popular. Although this program has improved access to care, participants have higher out-of-pocket expenditures for medications than those on employer-based plans across all localities. Across all groups, the uninsured bare the highest burden of expenditures, highlighting continued need to address health inequities for the most underserved populations.